Использования метода мозгового штурма при изучении специальных экологических дисциплин - Тихомирова, Татьяна Сергеевна; Филенко, Олеся Николаевна; Горбунова, Ольга Владимировна; Шестопалов, Алексей Валерьевич (Национальный технический университет "Харьковский политехнический институт", 2017)
У статті проаналізовано результтати екпериментального впровадження методу мозгового штурму для поушку рішень певних задач при проведенні практичних занять з спецальних екологічних дисциплін ("Ландшафтна екология", "Агроекологія", "Основи екології танеоекологія").

The results of the experimental introduction of the brainstorming method for solving the set tasks in practical classes on special ecological disciplines ("Landscape Ecology", "Agroecology", "Fundamentals of Ecology and Neoecology") are analyzed.
The brainstorm method using in special environmental disciplines studying
Keywords: МШ; участник; студент; практические занятия; экологические дисциплины